Becoming an acquirer and ecoming acquired - Lehto, Eero; Lehtoranta, Olavi (Työpapereita / Palkansaajien tutkimuslaitos, ISSN 1457-2923, 2002)
Tiivistelmä.
Keywords: Investments; företagsköp; forskning och utveckling; investeringar; investoinnit; tutkimus- ja kehittämistoiminta; yrityskaupat; company acquisitions; mergers; research and development